PROTOCOL: Prevalence and Risk and Protective Factors for Radicalization Among School‐Aged Youth: A Systematic Review - Anthony Petrosino; Claire Morgan (Campbell Systematic Reviews)
ABSTRACT This is a protocol for a Campbell systematic review. The objectives are to synthesize published and unpublished scientific literature on (1) the prevalence of and (2) the risk and protective factors for school‐aged youth radicalization. In the nascent field of research on radicalized youth, a priority of the review is to examine the breadth of empirical evidence on prevalence and risk and protective factors, and to identify gaps and opportunities for further research. Our research questions are: Part 1: Prevalence: What is the prevalence of radicalization among school‐aged youth? How does the prevalence of radicalization of school‐aged youth vary over time and by type of radical ideology (e.g., religiously motivated, far left and far right, ethno‐nationalist, racially and ethnically motivated, gender‐based, online conspiracy‐based)? Part 2: Risk and Protective Factors What are the cognitive and behavioral risk and protective factors for school‐aged youth radicalization? How do the cognitive and behavioral risk and protective factors for youth radicalization vary by type of radical ideology (e.g., religiously motivated, far left and far right, ethno‐nationalist, racially and ethnically motivated, gender‐based, online conspiracy‐based)?